2014
DOI: 10.1007/s10843-014-0138-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between entrepreneurial orientation and firm performance in large organizations over time

Abstract: The goal of this research paper is to study the possible interactions between operations strategy and entrepreneurial traits, performance and job satisfaction. This empirical paper used a non-experimental design to test a proposed model based on a review of relevant literature. The study was conducted with 1200 SMEs in the Lynchburg City region using an administered survey instrument. The results of this study indicate that entrepreneurial personality has statistically significant relationship with Performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 94 publications
(45 reference statements)
3
52
0
3
Order By: Relevance
“…: Grande et al 2011;Hafeez et al 2011;Chandrakumara et al 2011;Gupta and Gupta, 2015). For instance, by using a five-dimension EO model, Koe (2013) found that innovativeness, proactiveness, risk-taking, competitive aggressiveness and autonomy positively influenced the performance of government-linked companies (GLCs).…”
Section: Individual Entrepreneurial Orientation (Ieo)mentioning
confidence: 99%
“…: Grande et al 2011;Hafeez et al 2011;Chandrakumara et al 2011;Gupta and Gupta, 2015). For instance, by using a five-dimension EO model, Koe (2013) found that innovativeness, proactiveness, risk-taking, competitive aggressiveness and autonomy positively influenced the performance of government-linked companies (GLCs).…”
Section: Individual Entrepreneurial Orientation (Ieo)mentioning
confidence: 99%
“…Sarker and Palit (2015) identify whether there is any relationship between strategic orientation and the performance of small-and medium-sized enterprises operating in Bangladesh, and the results show that they are statistically significant with small-and medium-sized enterprises performance. Furthermore, Gupta and Gupta (2015) tried to understand the longitudinal relationship between entrepreneurial orientation and firm performance by studying analyses indicating that EO has a strong initial effect on firm performance.…”
Section: The Relationship Between Strategic Orientation and Organizatmentioning
confidence: 99%
“…The entrepreneurial orientation concept suggests that firms should be entrepreneurial in order to achieve superior performance [47]. This means that organizations need to have a strategic commitment to specific, observable actions in the form of innovation, proactiveness, and risk taking, and the strong support of those actions by top management [48]. According to [49] [50] [51], engaging in product-market innovation, being the first to enter new markets, and understanding risky ventures are at the heart of entrepreneurship.…”
Section: Entrepreneurial Orientationmentioning
confidence: 99%